Effectors as tools in disease resistance breeding against biotrophic, hemibiotrophic, and necrotrophic plant pathogens - Vleeshouwers, V.; Oliver, Richard (American Phytopathological Society, 2014)
One of most important challenges in plant breeding is improving resistance to the plethora of pathogens that threaten our crops. The ever-growing world population, changing pathogen populations, and fungicide resistance issues have increased the urgency of this task. In addition to a vital inflow of novel resistance sources into breeding programs, the functional characterization and deployment of resistance also needs improvement. Therefore, plant breeders need to adopt new strategies and techniques. In modern resistance breeding, effectors are emerging as tools to accelerate and improve the identification, functional characterization, and deployment of resistance genes. Since genome-wide catalogues of effectors have become available for various pathogens, including biotrophs as well as necrotrophs, effector-assisted breeding has been shown to be successful for various crops. “Effectoromics” has contributed to classical resistance breeding as well as for genetically modified approaches. Here, we present an overview of how effector-assisted breeding and deployment is being exploited for various pathosystems.